DNA-guided genome editing using structure-guided endonucleases. Issue 1 (December 2016) - Varshney, Gaurav; Burgess, Shawn
Abstract The search for novel ways to target and alter the genomes of living organisms accelerated rapidly this decade with the discovery of CRISPR/Cas9. Since the initial discovery, efforts to find alternative methods for altering the genome have expanded. A new study presenting an alternative approach has been demonstrated that utilizes flap endonuclease 1 (FEN-1) fused to the Fok1 endonuclease, which shows potential for DNA-guided genome targeting in vivo.